2016
DOI: 10.1002/minf.201501035
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Free Energy as a Molecular Descriptor in Drug Design: A Feasibility Study

Abstract: In this work the idea was investigated whether calculated hydration energy (ΔGhyd ) can be used as a molecular descriptor in defining promising regions of chemical space for drug design. Calculating ΔGhyd using the Density Solvation Model (SMD) in conjunction with the density functional theory (DFT) gave an excellent correlation with experimental values. Furthermore, calculated ΔGhyd correlates reasonably well with experimental water solubility (r(2) =0.545) and also log P (r(2) =0.530). Three compound collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…1521 Hydration free energies themselves are valuable quantities in drug design 43,78 and can be used to understand the impact of ligand desolvation on the binding process 79,80 or can be utilized as QSAR descriptors. 81 …”
Section: Hydration and Solvation Free Energies Have A Range Of Applicmentioning
confidence: 99%
“…1521 Hydration free energies themselves are valuable quantities in drug design 43,78 and can be used to understand the impact of ligand desolvation on the binding process 79,80 or can be utilized as QSAR descriptors. 81 …”
Section: Hydration and Solvation Free Energies Have A Range Of Applicmentioning
confidence: 99%
“…The other mainstream descriptors: molecular weight (MW), hydrogen bond donors (HD), hydrogen bond acceptors (HA) polar surface area (PSA) and rotatable bonds (RB) (see Table S1 in the Supplementary Materials ) are all within the drug-like chemical space. It has been previously noted that the currently-used molecular descriptors like log P and log S do not entirely capture the required water solubility profiles of successful drugs [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the degree of solubility in water of the studied molecule in comparison to 5-FU molecule is probably induced by the presence of the 1-(2-hydroxyethyl) fragment. Recently, Zafar et al [50] have estimated the range of Gibbs free energy of solvation in drug design; they have reported that the ûG sol value of quality drug candidates should be less than −12 Kcal/mol. the ûG sol value of the studied molecule is much less than −12 Kcal/mol.…”
Section: Nonlinear and Electronic Properties Gibbs Free Energy Of Somentioning
confidence: 99%